Weighting the Effects of Spatial Cognition and Activity Anchors on Time–Space Activity. Issue 1 (2nd January 2019) - Grinberger, A. Yair
Abstract : Many elements are known to affect the decision-making procedures that underlie time–space activity patterns. Yet, knowledge regarding the relations between these elements is lacking. In this article, a hierarchical structure of external and cognitive time–space behavioral influences is proposed based on the results of a field experiment. The experiment relied on an in situ sampling of stated and overt behaviors of visitors to a touristic site in northern Israel, using questionnaires and Global Positioning System loggers. Two experimental treatments were simultaneously applied during sampling, dividing the sample into four groups: Each participant received on entry one of two maps, designed according to different cartographical–cognitive approaches; new activity stations were placed during half of the sampling days, meaning that each participant was exposed to one of two possible spatial layouts. The behavioral patterns recorded expose each treatment's distinct behavioral effect along with its relative weight within the decision-making process, thus pointing toward a hierarchical structure.